2012
DOI: 10.5433/1679-0359.2012v33n5p1717
|View full text |Cite
|
Sign up to set email alerts
|

Efeito do gesso nas propriedades químicas do solo sob dois sistemas de manejo

Abstract: ResumoA combinação de gessagem e manejo do solo podem influenciar as propriedades químicas do solo. Neste contexto, o objetivo deste trabalho foi avaliar as propriedades químicas do solo submetido a dois manejos do solo e ao efeito residual de gesso, após 55 meses de implantação dos tratamentos. Desenvolvido em uma área experimental da FCA/UFGD de Dourados, MS, o experimento foi disposto no delineamento de blocos casualizados com os fatores arranjados em parcela subsubdividida. A parcelas, sub-parcelas e sub-s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
16
0
2

Year Published

2014
2014
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(24 citation statements)
references
References 17 publications
6
16
0
2
Order By: Relevance
“…Porém esse efeito não foi observado tanto aos 36 (Figura 1c) quanto aos 72 meses (Figura 2c) após a aplicação do gesso, corroborando com os dados encontrados por Souza et al (2012). A ausência de efeito da aplicação de gesso na lixiviação de K + pode ser explicada pela baixa formação do par iônico K 2 SO 4 0 (0,2 % do total solúvel) (Zambrosi et al, 2008).…”
Section: Resultados E Discussão Atributos Químicos Do Solounclassified
“…Porém esse efeito não foi observado tanto aos 36 (Figura 1c) quanto aos 72 meses (Figura 2c) após a aplicação do gesso, corroborando com os dados encontrados por Souza et al (2012). A ausência de efeito da aplicação de gesso na lixiviação de K + pode ser explicada pela baixa formação do par iônico K 2 SO 4 0 (0,2 % do total solúvel) (Zambrosi et al, 2008).…”
Section: Resultados E Discussão Atributos Químicos Do Solounclassified
“…Agricultural gypsum has been used as a tool to improve soil chemical properties, either by increasing Ca 2+ and S-SO 4 2-contents and the Ca 2+ /Mg 2+ ratio in the soil (MASCHIETTO, 2009;RAMPIM et al, 2011;SOUZA et al, 2012;TRINDADE, 2013) or by altering the toxic aluminum forms in the soil subsurface (RAMPIM et al, 2011). These amendments lead to increased plant height (CUSTÓDIO et al, 2005;SOUZA et al, 2010), increased production of dry matter (CUSTÓDIO et al, 2005;CRUSCIOL, 2008), higher nutrient absorption efficiency (CAIRES et al, 2006;CUSTÓDIO et al, 2005;RAMPIM et al, 2011), and consequently, better grain quality (CAIRES et al, 2006).…”
Section: Introductionmentioning
confidence: 99%
“…Souza et al (2012) found that NT promoted an increase in Ca 2+ contents in the 0.00-0.10 m layer in a Distroferric Red Ferralsol under different management systems, with and without application of gypsum. Surface accumulation of Ca 2+ may be associated with the surface application of lime and the higher ionic strength of this cation in solution, as well as preferential adsorption of divalent cations compared to monovalent cations (Freire et al, 2003;Wiethölter, 2007).…”
Section: Resultsmentioning
confidence: 91%
“…However, the cumulative percentage of variance explained by the first two principal components was greater on the surface than in the subsurface: 90.7 % in the 0.00-0.05 m layer, 79.8 % in the 0.05-0.10 m layer, and 83.1 % in the 0.10-0.30 m layer. It is possible that this decrease in the explanatory potential of PCA regarding variation in the data with depth is linked to the fact that the properties analyzed are affected by soil management systems and/or cover crops (DeMaria et al, 1999;Ciotta et al, 2002;Schlindwein and Anghinoni, 2002;Santos et al, 2008;Costa et al, 2009;Souza et al, 2012;Vieira et al, 2013), and this effect is more intense in the upper layer of the soil profile. Typically, in deeper layers, the effects of management and/or cover crop systems are smaller, and it is possible that pedogenetic properties are of greater intensity, for example, the texture and mineralogy of the soil, leading to less explanatory power through chemical properties sensitive to changes in land use and occupation.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation